Description of Asphyxia Incidents with Umbilical Cord Entanglement in Newborns in the Work Area of the Health Center in Bantaeng - Hanifah, Astin Nur; Rahmadhani, Sendy Pratiwi; Parwati, Dewi; Saputra, M. Khalid Fredy; Asmin, Risna Yunita; Thalib, Kiki Uniatri; Wahyuni, Sri (International Journal of Health Sciences, 2024)
Asphyxia neonatorum is a condition where a newborn baby does not breathe spontaneously and regularly after birth. Asphyxia can occur during pregnancy and childbirth. Asphyxia in newborns is a high risk because they have a greater chance of experiencing the baby's death or becoming seriously ill during the neonatal period. The aim of this research is to determine the description of the incidence of asphyxia based on risk factors for mothers, babies and birth factors at the Community Health Center. This research method was carried out descriptively using secondary data at the Community Health Center to find out the general picture of the incidence of asphyxia in newborns with research variables which include risk factors for mother, baby and childbirth. The results show that factors related to the incidence of asphyxia in community health centers are influenced by risk factors for mother, baby and childbirth.